Discharge Identity of Medullary Inspiratory Neurons is Altered during Repetitive Fictive Cough - Segers, L. S. (Frontiers Research Foundation, 2012)
This study investigated the stability of the discharge identity of inspiratory decrementing (I-Dec) and augmenting (I-Aug) neurons in the caudal (cVRC) and rostral (rVRC) ventral respiratory column during repetitive fictive cough in the cat. Inspiratory neurons in the cVRC (n = 23) and rVRC (n = 17) were recorded with microelectrodes. Fictive cough was elicited by mechanical stimulation of the intrathoracic trachea. Approximately 43% (10 of 23) of I-Dec neurons shifted to an augmenting discharge pattern during the first cough cycle (C1). By the second cough cycle (C2), half of these returned to a decrementing pattern. Approximately 94% (16 of 17) of I-Aug neurons retained an augmenting pattern during C1 of a multi-cough response episode. Phrenic burst amplitude and inspiratory duration increased during C1, but decreased with each subsequent cough in a series of repetitive coughs. As a step in evaluating the model-driven hypothesis that VRC I-Dec neurons contribute to the augmentation of inspiratory drive during cough via inhibition of VRC tonic expiratory neurons that inhibit premotor inspiratory neurons, cross-correlation analysis was used to assess relationships of tonic expiratory cells with simultaneously recorded inspiratory neurons. Our results suggest that reconfiguration of inspiratory-related sub-networks of the respiratory pattern generator occurs on a cycle-by-cycle basis during repetitive coughing.